A analytic and numerical solution to a modified Kawahara equation and a convergence analysis of the method - Polat, Necat; Kaya, Dogan; Tutalar, H. Ilhan (Elsevier Science Inc, 2006)
In this paper, we present an Adomian's decomposition method (shortly ADM) for numerical approximation traveling-wave solutions of the modified Kawahara equation. The numerical solutions are compared with the known analytical solutions. We also prove the convergence of Adomian decomposition method (ADM) applied to the modified Kawahara equation. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: modified Kawahara equation; traveling wave solution; numerical solution; convergence analysis; Adomian decomposition method